Localized coupling effects and multiphysics modeling for the laser ablation behavior of composite structure subjected to high-speed airflow - Wang, Ruixing; Wang, Zhe; Ma, Te; Yuan, Wu; Cui, Yue; Song, Hongwei (International journal of thermal sciences, 2023)
When the composite structure is subjected to high-power laser irradiation and high-speed airflow, its ablation behavior presents significant localized characteristics and strong coupling effect. In this work, a coupled fluid-thermal-ablation model is developed to quantitatively investigate the localized coupling effects. Here a loosely coupled scheme with second order temporal accuracy is utilized to improve the coupling efficiency, and a high-quality mesh reconstruction method combining the Arbitrary Lagrange-Euler (ALE) algorithm and Radial Basis Function (RBF) interpolation algorithm is established to capture the moving boundary of the localized ablation pit with large deformation. The model is validated by simulating the laser ablation behavior of C/SiC composite plate subjected to the hypersonic airflow, and the predicted ablation pit profile shows a good agreement with the available experimental result. Analytical results show that as the evolution of the localized asymmetric ablation pit induces transformation of the flow regime from a closed pit flow to an open pit flow. Moreover, the flow regime transition would remarkably alter the localized flow characteristics, including the local static pressure and dynamic pressure, which in turn significantly affects the sublimation and mechanical erosion rates of C/SiC composite plate, respectively. •Coupled numerical model for the localized laser ablation behavior of composite structure subject to airflow is developed.•Coupled strategy with second order temporal accuracy and mesh deformation method combining ALE and RBF are established.•The predicted ablation profile agrees well with the experimental result.•The pit flow would change from closed pit flow to open pit flow as the localized ablation pit evolves.•Flow regime transition remarkably alters the localized flow characteristics, which in turn affects the ablation mechanisms.